Dhamma in Practice: The Life of Vessantara (Bodhi Path, 2024)
Dhamma, this phrase, and the ideas it is based on have been the most important aspect of Indian civilization throughout the ages. Regardless of linguistic, sectarian, or geographical variances, the fundamental idea of Indian religion and culture has always revolved around Dhamma. According to Buddhism, Dhamma often stands for, law, duty, righteousness, a goal of life (Puruṣārtha), cause, spiritual texts, quality, and religious teaching, good conduct, and behavior. Dhamma is a way of religious practice, a revered object of devotion whose properties are to be remembered and thought about by the practitioner to inspire faith and generate serenity; it is a transcendent reality and ‘salvific Truth’. In the present context, Dhamma is more widely used as good conduct or proper behavior.In Buddhism, good conduct isn't just about avoiding harm, it's about actively alleviating suffering (dukkha) in the world. The ultimate embodiment of this ideal is the Bodhisatta, the future Buddha. Vessantara Jātaka presents a powerful example of sacrifice, where the protagonist, Prince Vessantara, embodies the pinnacle of generosity. He doesn't just give to those in need – he gives everything, even his most prized possessions and cherished family, leading to his own exile. This, scholars aptly call "atī-dāna," generosity beyond measureThis monograph at hand will elucidate the concept of Dhamma and how to inculcate Bodhisatta Vessantara's practice of Dhamma for the benefit of society
Keywords: Dhamma; Vessantara; Vessantara Jātaka; The Buddha